Beyond Sustainability: Community Based Tourism and Governance Dynamics in Central Lombok Regency, Indonesia - Ilham Zitri; Firzhal Arzhi Jiwantara; Rifaid Rifaid; Meida Mutiarani Rizkia; Muhammad Rizki Smith (Jurnal Pemerintahan dan Politik Lokal, 2026)
Tourism development in Central Lombok Regency has experienced significant acceleration following the designation of the Mandalika Special Economic Zone (KEK) as a national super-priority tourism destination. Despite its positive impact on economic growth and investment, this tourism development has not yet fully provided equitable benefits to local communities, particularly buffer-village communities. This study aims to analyze the dynamics of community-based tourism governance from a perspective beyond sustainability, emphasizing the roles of actors, network relationships, and opportunities to strengthen Community-Based Tourism (CBT) in Central Lombok Regency. The study used a qualitative approach, with data collected through in-depth interviews, participatory observation, Focus Group Discussions (FGDs), and a review of regional planning documents. Data analysis was conducted using a Social Network Analysis (SNA) approach to map the structure and roles of actors in tourism governance. The results show that the tourism governance network remains centralized on institutional actors and area managers, while local communities are in a peripheral position. The results show that the tourism governance network remains centralized on institutional actors and area managers, while local communities are positioned at the periphery. However, this study is limited by its focus on a single regional case and the use of cross-sectional network data, which restricts the ability to capture longitudinal governance dynamics and comparative patterns across destinations. Future research is therefore recommended to employ multi-site comparative designs and longitudinal Social Network Analysis to examine how governance structures evolve and to assess the impacts of policy interventions on community empowerment. In addition, integrating quantitative socio-economic indicators with network analysis would provide a more comprehensive understanding of how governance configurations influence livelihood outcomes. Such extensions would strengthen empirical evidence for advancing regenerative tourism models that genuinely place local communities at the center of tourism development.